KETERKAITAN TEORI DAN RISET EMPIRIS: SUATU PENDEKATAN THEORY-SETTING-TESTABLE HYPOTHESIS MODEL - Soliha, Euis (Faculty of Economics and Business Universitas Jenderal Soedirman, 2011)
This paper tries comments interrelationship of theory and empirical research with approach of Theory-Setting-Testable Hypothesis Model. Theory-Setting-Testable model explains about three development stages related to hypothesis. Theory-Setting-Testable model appropriate to applied research to building theory. Process three development stages connected by hypothesis started with theory phase and identification of theoretical statements connecting independent variable and dependent variable. Phase secondly relates to hypothesis expansion. Third phase by replacing concept in proposition with definition of operational and tests statistic relation between concept.